The Africa Center for Biostatistical Excellence: a proposal for enhancing biostatistics capacity for sub‐Saharan Africa. (3rd July 2015) - Machekano, Rhoderick; Young, Taryn; Rusakaniko, Simbarashe; Musonda, Patrick; Sartorius, Ben; Todd, Jim; Fegan, Greg; Thabane, Lehana; Chikte, Usuf
Abstract : Sub‐Saharan Africa has a shortage of well‐trained biomedical research methodologists, in particular, biostatisticians. In July 2014, a group of biostatisticians and researchers from the region attended a brainstorming workshop to identify ways in which to reduce the deficit in this critical skill. The workshop recognized that recommendations from previous workshops on building biostatistics capacity in sub‐Saharan Africa had not been implemented. The discussions culminated with a proposal to setup an Africa Center for Biostatistical Excellence, a collaborative effort across academic and researcher institutions within the region, as a vehicle for promoting biostatistics capacity building through specialized academic masters programs as well as regular workshops targeting researchers. Copyright © 2015 John Wiley & Sons, Ltd.